Human albumin solution utilization patterns prior and during COVID-19 pandemic in United Arab Emirates: Time to develop and implement national guideline on prescribing and utilization - Mohammed Sallam; Johan Snygg (Narra Sains Indonesia, 2022)
The human albumin solution (HAS) has limited but important indications in clinical practice. However, the inappropriate use of HAS can be costly. Thus, it is imperative to establish a practical protocol to use albumin products and rationalize its usage. The aim of this study was to identify albumin utilization patterns in a multi-specialty private hospital in Dubai, United Arab Emirates (UAE), before and during the COVID-19 epidemic in the country. In addition, the objectives were to demonstrate the importance of reconsidering the prescribing strategies for albumin administration. All data on 20% HAS administration in Mediclinic Welcare Hospital were retrieved during January 2019–May 2021, including the total quantities administered and data on primary diagnosis. A total of 579 patient admissions with several diagnoses were included in the study. The percentage of clinically indicated 20% HAS administration decreased from 13.0% in the pre-COVID-19 phase to 1.5% in the COVID-19 phase (P<0.001). An increase in the administration of 20% HAS not backed by agreed clinical evidence followed the increase in new number of COVID-19 cases in the UAE. The current study showed a large proportion of administered HAS, that drastically increased during COVID-19 with lack of clear evidence of its benefit. This pilot study should be followed by refining of the institutional guidelines of HAS use, frequent audits and interactive educational interventions. In turn, the refinement of HAS administration guidelines can help to reduce the unjustified cost of inappropriate HAS use.